Operation Submaximal (Extremally Disconnected) Spaces - Sudha, P (Annals of the Romanian society for cell biology, 2021)
Introduction Soft set theory [11] was firstly introduced by Molodtsov in 1999 as a general mathematical tool for dealing with uncertain, fuzzy, not clearly defined objects. [12] presented some new definitions on soft sets such as a subset, the complement of a soft set and discussed in detail the application of soft set theory in decision making problems [13]. Preliminaries Let U be an initial universe set and EU be a collection of all possible parameters with respect to U, where parameters are the characteristics or properties of objects in U. We will call Eu the universe set of parameters with respect to U. Definition 2.1. Henceforth, let X be an initial universe set and E be the fixed nonempty set of parameter with respect to X unless otherwise specified.